Databases in clinical practice. Issue 2 (February 2023) - Plummer, Nicholas R.
Abstract: A database is a structured collection of data. Databases allow clinical data to be stored in a reliable and accessible way for clinical care, research, and quality improvement. Such databases are typically made up of one or more tables, each consisting of rows of instances described by columns of fields. Relational databases improve performance and data integrity by utilizing multiple linked tables to remove duplication of data and provide constraints on how data is related. Structure query language can be used to manipulate relational databases, and retrieve the response to queries in the form of a new table.